Binary-phased nanoparticles for enhanced thermoelectric properties - Zhang, Hua (2012)
Binary-phased PbTe-PtTe2 nanoparticles are synthesized by co-precipitation in a chemical process. These nanoparticles show much enhanced power factors as compared to that of pure PbTe nanoparticles, which may give impact on development of new types of highly efficient thermoelectric materials.